Thermochromism in a dinuclear copper complex by spin state changes at various temperatures. (1st January 2022) - Hamaguchi, Tomohiko; Matsuda, Yutaro; Satomi, Naoki; Ishikawa, Ryuta; Hayami, Shinya; Ando, Isao; Kawata, Satoshi
Graphical abstract: Thermochromism in a dinuclear copper complex was assessed by spin state changes and colour changes at various temperatures. Highlights: A dinuclear Cu complex was synthesized and characterized. The complex shows thermochromism in the solid state. The complex does not show structural change depends on the temperature. The thermochromism was assessed by TD-DFT calculation. Spin state change at various temperatures would cause the thermochromism. Abstract: This study explored the thermochromic behavior of [(μ2 -6-methyl-2-pyridinemethanolate)2 {Cu(6-methyl-2-pyridinemethanol)}2 ](PF6 )2 . The complexes show no significant variation between 296 K and 100 K according to a single-crystal X-ray crystallographic investigation. The occupancy of the triplet at 300 K and 100 K is 55% and 16.9%, respectively based on magnetic susceptibility. Photographs of the complex at different temperatures and quantum calculation exhibit that the thermochromic behavior is induced by the alteration of spin state between triplet and singlet.